Draft Seventh Five Year Plan Andhra Pradesh 1985-90 Volume II (Section III Rural Development) Government of Andhra Pradesh - Planning Commission (Planning Commission, 1985)
In the Fourth Plan Period, based on the recommendations of the Committee, the Government of India have sanctioned 3 S.F.D.As., and 2 M.F.A.L.D.As., to Andhra Pradesh. These Agencies were organised in Srikakulam, Cuddapah, Nalgonda and Visakhapatnam Districts. There was composite scheme in Nalgonda District. The five agencies in four districts completed their first phase of 5 year period by 31-3-1976 For the remaining 3 years of Fifth Plan, three Agencies were permitted to be continued with an outlay of Rs. 100.00 lakhs and the M.F.A.L.D.A.
Finance and Planning (PLG. Wing) Department, Government of Andhra Pradesh